Method for producing a polyacetal resin composition
Patent Information
- Application Number
- CN202580024473.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-30
AI Technical Summary
[0019]根据本发明,能够提供:刚性和抗蠕变特性优异的聚缩醛树脂组合物的制造方法。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to a method for manufacturing polyacetal resin compositions. Background Technology
[0002] Polyacetal resins offer an excellent balance of mechanical properties, chemical resistance, and lubrication, and are easy to process. Therefore, they are widely used as engineering plastics, primarily in electrical / electronic components, automotive parts, and various other mechanical components. In recent years, with the expansion and diversification of applications, the required properties of polyacetal resins have become increasingly sophisticated. Therefore, there is a demand for polyacetal resins that maintain excellent flowability, moldability, thermal stability, and lubrication while also possessing rigidity and creep resistance.
[0003] As a method for obtaining polyacetal resin with the above-mentioned properties, the methods disclosed in Patent Documents 1 and 2 are known. However, in order to meet the required properties of polyacetal resin, further improvements in rigidity and creep resistance are required.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-342442
[0007] Patent Document 2: Japanese Patent No. 7179046 Summary of the Invention
[0008] The problem the invention aims to solve
[0009] The present invention has been made in view of the above aspects, and its object is to provide a method for manufacturing a polyacetal resin composition with excellent rigidity and creep resistance.
[0010] Solution for solving the problem
[0011] The inventors conducted in-depth research and found that the above-mentioned problems could be solved, thus completing the present invention. Specifically, the present invention is constructed as described in [1] to [6] below.
[0012] [1] A method for manufacturing a polyacetal resin composition, comprising the following steps:
[0013] Step (I) involves copolymerizing 0.05 to 5 parts by weight of a cyclic acetal compound (b) with 0.001 to 0.5 parts by weight of an aliphatic glycidyl ether compound (c) having a chlorine content of 4% by weight or more, in the presence of a linear formaldehyde compound (d), to produce a polyacetal copolymer (A). Step (II) involves copolymerizing 97.0 to 99.5% by weight of a trioxane (a') with 0.5 to 3.0% by weight of the cyclic acetal compound (b') to produce a linear polyacetal resin (B). Step (III) involves mixing 0.1 to 10 parts by weight of the aforementioned polyacetal copolymer (A) with 100 parts by weight of the aforementioned linear polyacetal resin (B). The mass fraction is melt-blended, wherein the aforementioned aliphatic glycidyl ether compound (c) is selected from at least one of the group consisting of trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, and pentaerythritol tetraglycidyl ether. The aforementioned step (I) further comprises the following step: setting the total mass [g] of the aforementioned (a), (b), and (c) as α, the number of moles of the aforementioned (d) as β, the total number of moles of water contained in the aforementioned (a), (b), and (c) as γ, and the total number of moles of methanol as δ, such that (β+γ+δ) / α is less than 10 μmol / g, and calculating the aforementioned chlorine content by using a quantitative method based on the determination intensity of fluorescence X-rays.
[0014] [2] The method for manufacturing the polyacetal resin composition according to [1], wherein the aforementioned cyclic acetal compounds (b) and (b') are 1,3-dioxolane or 1,4-butanediol formaldehyde.
[0015] [3] A method for manufacturing a polyacetal resin composition according to any one of [1] or [2], wherein the aforementioned linear acetal compound (d) is at least one selected from the group consisting of dimethoxymethane, diethoxymethane and dibutoxymethane.
[0016] [4] The method for manufacturing the polyacetal resin composition according to any one of [1] to [3], wherein the melt flow rate of the aforementioned linear polyacetal resin (B) is 1 to 50 g / 10 minutes.
[0017] [5] A polyacetal resin composition, which is manufactured by any one of [1] to [4].
[0018] The effects of the invention
[0019] According to the present invention, a method for manufacturing a polyacetal resin composition with excellent rigidity and creep resistance can be provided. Detailed Implementation
[0020] The embodiments of the present invention will be described in detail below, but the present invention is not limited to the following embodiments.
[0021] <Method for manufacturing polyacetal resin composition>
[0022] The method for manufacturing the polyacetal resin composition includes the following steps: step (I) of manufacturing a polyacetal copolymer (A); step (II) of manufacturing a linear polyacetal resin (B); and step (III) of melt-blending the polyacetal copolymer (A) and the linear polyacetal resin (B). Each step will be described in detail below.
[0023] [Process (I)]
[0024] Process (I) is as follows: relative to 100 parts by weight of trioxane (a), 0.05 to 5 parts by weight of cyclic acetal compound (b) and 0.001 to 0.5 parts by weight of aliphatic glycidyl ether compound (c) with a chlorine content of 4% by weight or more are copolymerized in the presence of linear formaldehyde compound (d) to produce polyacetal copolymer (A).
[0025] Trioxane(a)
[0026] Trioxane is a cyclic trimer of formaldehyde. It should be noted that trioxane is typically obtained by reacting an aqueous solution of formaldehyde in the presence of an acidic catalyst, followed by purification through distillation or other methods.
[0027] Cyclic Acetal Compounds (b)
[0028] Cyclic acetals are compounds with two or more carbon atoms in the ring and are capable of copolymerizing with trioxane.
[0029] Examples of cyclic acetal compounds include: ethylene oxide, propylene oxide, epibutylene oxide, epichlorohydrin, epibromopropane, styrene oxide, oxetane, 3,3-bis(chloromethyl)oxetane, tetrahydrofuran, trioxetane-heptane, 1,3-dioxolane, ethylene glycol formaldehyde, propylene glycol formaldehyde, diethylene glycol formaldehyde, triethylene glycol formaldehyde, 1,4-butanediol formaldehyde, 1,5-pentanediol formaldehyde, and 1,6-hexanediol formaldehyde. Among these, 1,3-dioxolane and 1,4-butanediol formaldehyde are preferred.
[0030] The content of the cyclic acetal compound (b) is 0.05 to 5 parts by mass relative to 100 parts by mass of trioxane (a). More preferably, the content of the cyclic acetal compound (b) is 1 to 5 parts by mass.
[0031] Aliphatic glycidyl ether compounds (c)
[0032] Aliphatic glycidyl ether compounds have structures that can form branched or cross-linked structures in the backbone of polyacetal copolymers.
[0033] In one embodiment of the present invention, the aliphatic glycidyl ether compound is at least one selected from the group consisting of trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, and pentaerythritol tetraglycidyl ether. By selecting an aliphatic glycidyl ether compound from the above compounds, a polyacetal resin composition with excellent rigidity and creep resistance can be manufactured.
[0034] In one embodiment of the present invention, the aliphatic glycidyl ether compound is an aliphatic glycidyl ether compound with a chlorine content of 4% by weight or more. By using an aliphatic glycidyl ether compound with a chlorine content of 4% by weight or more, it is possible to manufacture a polyacetal resin composition with excellent rigidity and creep resistance.
[0035] In addition, the chlorine content is preferably 4% by weight or more and 10% by weight or less, more preferably 4% by weight or more and 8.5% by weight or less.
[0036] The chlorine content of aliphatic glycidyl ether compounds was calculated using a fluorescence X-ray analysis device, based on the intensity of the fluorescence X-rays, using a quantitative method employing the basic parameter (FP) method.
[0037] The aliphatic glycidyl ether compound with a chlorine content of 4% by weight or more is present in an amount of 0.001 to 0.5 parts by weight relative to 100 parts by weight of trioxane. By making the content of the aliphatic glycidyl ether compound (c) 0.001 to 0.5 parts by weight, a polyacetal resin composition with excellent rigidity and creep resistance can be manufactured.
[0038] In addition, the content of the above-mentioned aliphatic glycidyl ether compound is preferably 0.01 to 0.5 parts by weight, more preferably 0.05 to 0.5 parts by weight.
[0039] Linear formaldehyde compounds (d)
[0040] In one embodiment of the present invention, a linear formaldehyde compound is used as a molecular weight regulator.
[0041] Examples of linear formaldehydes include: methylal, ethylal, dibutoxymethane, bis(methoxymethyl) ether, bis(ethoxymethyl) ether, bis(butoxymethyl) ether, etc. Among these, methylal, ethylal, or dibutoxymethane are preferred.
[0042] The content of linear acetal compounds can be appropriately set according to the desired molecular weight of the polyacetal copolymer (A).
[0043] In addition, process (I) includes the following steps: the total mass [g] of trioxane (a), cyclic acetal compound (b) and aliphatic glycidyl ether compound (c) is set as α, the number of moles of linear formaldehyde compound (d) is set as β, the total number of moles of water contained in (a), (b) and (c) is set as γ, and the total number of moles of methanol is set as δ, such that (β+γ+δ) / α is 10 μmol / g or less.
[0044] By setting the (β+γ+δ) / α ratio to below 10 μmol / g, a polyacetal resin composition with excellent rigidity and creep resistance can be manufactured. It should be noted that the water and methanol contained in (a), (b), and (c) above originate from various impurities.
[0045] In addition, (β+γ+δ) / α is preferably 3~10 μmol / g, more preferably 4~8 μmol / g.
[0046] Method for manufacturing polyacetal copolymer (A)
[0047] Polyacetal copolymer (A) can be manufactured by continuously feeding trioxane (a), cyclic acetal compound (b), aliphatic glycidyl ether compound (c) and linear formaldehyde compound (d) into a bulk polymerization process under specified conditions using a known method and polymerization apparatus in the presence of a cationic polymerization catalyst.
[0048] Examples of polymerization equipment include batch and continuous types. In batch types, commonly used reaction tanks with agitators can be used. In continuous types, co-kneaders, twin-screw continuous extrusion mixers, twin-screw paddle extruders, and twin-screw extruders with vents can be used. Industrially, the preferred manufacturing method is the continuous type.
[0049] (Catonic polymerization catalyst)
[0050] Examples of cationic polymerization catalysts include Lewis acids and protic acids.
[0051] Examples of Lewis acids include: boron trifluoride, tin tetrachloride, titanium tetrachloride, phosphorus pentafluoride, phosphorus pentachloride, antimony pentafluoride and their complexes or salts.
[0052] Examples of protic acids include: perfluoroalkyl sulfonic acids, heteropoly acids, and isopoly acids.
[0053] Examples of perfluoroalkane sulfonic acids include: trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoropropanesulfonic acid, nonafluorobutanesulfonic acid, undecylfluoropentanesulfonic acid, tridecafluorohexanesulfonic acid, pentadecylfluoroheptanesulfonic acid, and heptadecafluorooctanesulfonic acid. Examples of heteropoly acids include: phosphotungstic acid, phosphomolybdic acid, phosphomolybdic tungstate, phosphomolybdic vanadate, phosphomolybdic tungstate, phosphomolybdic vanadate, phosphomolybdic vanadate, silicotungstic acid, silicotungstate, silicotungstate, silicotungstate, silicotungstate, silicotungstate, silicotungstate, silicotungstate, silicotungstate. Examples of isopoly acids include: paratungstic acid, metatungstic acid, paramolybdic acid, metamolybdic acid, metavanadate, and isopolyvanadate.
[0054] The amount of cationic polymerization catalyst added is preferably 0.1 ppm or more relative to the total amount of all monomers. Furthermore, there is no particular upper limit to the amount of polymerization catalyst added, but it is preferably 100 ppm or less.
[0055] [Process (II)]
[0056] Step (II) is a step of manufacturing linear polyacetal resin (B) by copolymerizing 97.0 to 99.5% by weight of trioxane (a') with 0.5 to 3.0% by weight of cyclic acetal compound (b').
[0057] The content of trioxane (a') is preferably 98.0 to 99.0% by weight.
[0058] The cyclic acetal compound (b') may be selected from the above-mentioned cyclic acetal compound. Furthermore, the content of the cyclic acetal compound (b') is preferably 1.0 to 2.5% by weight.
[0059] By setting the contents of trioxane (a') and cyclic acetal compound (b') as described above, the melt flow rate (MFR) described later can be made to be within the desired range.
[0060] The MFR of the linear polyacetal resin (B) is preferably 1 to 50 g / 10 min, more preferably 1 to 40 g / 10 min, and particularly preferably 2 to 35 g / 10 min. By using the linear polyacetal resin (B) with an MFR of 1 to 50 g / 10 min, it is possible to manufacture polyacetal resin compositions with excellent rigidity and creep resistance.
[0061] The MFR of linear polyacetal resin (B) can be determined, for example, using a melt indexer L220 (manufactured by TATEYAMAKAGAKU HIGH-TECHNOLOGIES CO., LTD).
[0062] Method for manufacturing linear polyacetal resin (B)
[0063] Linear polyacetal resin (B) can be manufactured using known methods and the aforementioned batch, continuous, and other polymerization apparatus.
[0064] [Process (III)]
[0065] Step (III) is as follows: relative to 100 parts by weight of linear polyacetal resin (B), 0.1 to 10 parts by weight of polyacetal copolymer (A) are mixed and melt-blended to produce a polyacetal resin composition.
[0066] Method for manufacturing polyacetal resin compositions
[0067] The polyacetal resin composition can be manufactured as follows: using a known method and the above-mentioned batch, continuous or other polymerization apparatus, the polyacetal copolymer (A) and the linear polyacetal resin (B) are melt-blended at a temperature of 180 to 270°C for at least 30 seconds.
[0068] Other Additives
[0069] It should be noted that the polyacetal copolymers, linear polyacetal resins, and polyacetal resin compositions obtained in steps (I) to (III) may contain various known stabilizers / additives.
[0070] Examples of stabilizers include: hindered phenolic compounds, hindered amine compounds, nitrogen-containing basic compounds, oxides of alkali metals or alkaline earth metals, hydroxides, inorganic salts, carboxylates, etc. Examples of additives include: dyes, pigments and other colorants, fluorescent whitening agents, lubricants, nucleating agents, release agents, antistatic agents, surfactants, etc.
[0071] <Polyacetal Resin Composition>
[0072] The polyacetal resin composition manufactured through the above processes (I) to (III) has excellent mechanical properties, including rigidity and creep resistance.
[0073] Example
[0074] The present invention will now be described in detail with reference to embodiments, but the present invention is not limited thereto.
[0075] <Method for manufacturing polyacetal copolymer (A)>
[0076] Bulk polymerization was carried out using a continuous mixing reactor consisting of a jacket on the outside for passing hot (cold) media, a barrel with two overlapping circular sections in cross-section, and a rotating shaft with blades. The two rotating shafts of the polymerizer were rotated at a constant speed, with the circumferential speed of the blade tips at 0.5 m / s. Simultaneously, trioxane (a), a cyclic acetal compound (b), an aliphatic glycidyl ether compound (c), and a linear formal compound (d) were continuously supplied in the amounts shown in Table 1. A homogeneous mixture of boron trifluoride gas, containing the catalyst, was also continuously supplied, with the boron trifluoride conversion relative to trioxane being 0.005% by mass. The reaction product discharged from the polymerizer was rapidly passed through a crusher and added to an aqueous solution containing 0.1% by mass of triethylamine at 80°C to deactivate the catalyst. After separation, washing, and drying, a crude polyacetal copolymer was obtained.
[0077] Add 0.3 parts by mass of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and 0.15 parts by mass of melamine as stabilizers to 100 parts by mass of the crude polyacetal copolymer obtained by the above method, and melt-blend using a twin-screw extruder at 210°C to obtain polyacetal copolymers A-1 to A-14.
[0078] <Method for manufacturing linear polyacetal resin (B)>
[0079] Using the continuous mixing reactor described above, trioxane (a') and cyclic acetal compound (b') were continuously supplied in the amounts shown in Table 2, and boron trifluoride as a catalyst was continuously supplied relative to trioxane at 0.005% by weight. Bulk polymerization was carried out. The reaction products discharged from the polymerizer were treated in the same way as described above, thereby obtaining linear polyacetal resins B-1 to B-7.
[0080] <Method for manufacturing polyacetal resin composition>
[0081] Polyacetal copolymer (A) and linear polyacetal resin (B) were melt-blended using a twin-screw extruder at 210°C in the amounts shown in Tables 3-5 to obtain polyacetal resin compositions 1-27.
[0082] <Quantitative Method for Chlorine Content>
[0083] The aliphatic glycidyl ether compounds c-1 to c-5 in Table 1 were respectively placed into liquid determination containers, and the results were calculated using the FP method with a fluorescence X-ray analysis device.
[0084] Measurement Conditions
[0085] Measurement apparatus: ZSX Primus IV (manufactured by Rigaku Corporation)
[0086] Measurement type: EZ scan
[0087] Sample type: Liquid
[0088] Component form: Metal
[0089] Balance: C9H 10 O3
[0090] Sample film absorption correction: P.E. Film
[0091] Impurity correction: None
[0092] Matching library: None
[0093] Helium atmosphere correction: Yes
[0094] <MFR Measurement Method>
[0095] The MFR (g / 10 min) of the linear polyacetal resin (B) in Table 2 was measured using a melt index tester Model L220 manufactured by TATEYAMA KAGAKU HIGH-TECHNOLOGIES CO., LTD.
[0096] In addition, the abbreviations and symbols in Tables 1 to 5 are described below.
[0097] DO: 1,3-dioxolane
[0098] BDF: Butanediol formal
[0099] MFR: Melt flow rate
[0100] c-1: Trimethylolpropane triglycidyl ether (chlorine content: 6.3% by weight)
[0101] c-2: Trimethylolpropane triglycidyl ether (chlorine content: 7.9% by weight)
[0102] c-3: Glycerol triglycidyl ether (chlorine content: 4.2% by weight)
[0103] c-4: Pentaerythritol tetraglycidyl ether (chlorine content: 7.0% by weight)
[0104] c-5: Trimethylolpropane triglycidyl ether (chlorine content: 3.5% by weight)
[0105] MeAL: Dimethoxymethane
[0106] EtAL: Diethoxymethane
[0107] DBM: Dibutoxymethane
[0108] [evaluate]
[0109] For polyacetal resin compositions 1-27, tensile tests and creep properties were evaluated as shown below. The evaluation results are shown in Tables 3-5.
[0110] <Evaluation of Tensile Test>
[0111] Polyacetal resin compositions 1-27 were fed into an injection molding machine, and type A test pieces were prepared according to ISO 3167. Tensile strength was determined using these test pieces according to ISO 527-1,2.
[0112] <Evaluation of Creep Properties>
[0113] Using polyacetal resin compositions 1-27, test pieces were prepared using the same method as those prepared in the tensile test evaluation. Using a creep testing machine, a load of 21 MPa was applied at 80°C in the atmosphere as a high-temperature, high-load condition, and the time (hr) until the test piece broke was measured.
[0114] [Table 1]
[0115]
[0116] [Table 2]
[0117]
[0118] [Table 3]
[0119]
[0120] [Table 4]
[0121]
[0122] [Table 5]
[0123]
[0124] As shown in Tables 3-5, it can be seen that by using a polyacetal copolymer (A) that utilizes an aliphatic glycidyl ether compound with a chlorine content of 4% by weight or more, a polyacetal resin composition with excellent rigidity and creep resistance can be manufactured.
[0125] Industrial availability
[0126] According to the present invention, the polyacetal resin composition of the present invention has excellent mechanical properties, and therefore is expected to contribute to the progress and popularization of polyacetal resin compositions.
Claims
1. A method for manufacturing a polyacetal resin composition, comprising the following steps: In step (I), in the presence of linear formaldehyde compound (d), 0.05 to 5 parts by mass of cyclic acetal compound (b) and 0.001 to 0.5 parts by mass of aliphatic glycidyl ether compound (c) with a chlorine content of 4% by weight or more are copolymerized relative to 100 parts by mass of trioxane (a) to produce polyacetal copolymer (A). Step (II) involves copolymerizing 97.0–99.5% by weight of trioxane (a') with 0.5–3.0% by weight of a cyclic acetal compound (b') to produce a linear polyacetal resin (B); and, In step (III), 0.1 to 10 parts by weight of the polyacetal copolymer (A) are mixed with 100 parts by weight of the linear polyacetal resin (B) and then melt-blended. The aliphatic glycidyl ether compound (c) is at least one selected from the group consisting of trimethylolpropane triglycidyl ether, glycerol triglycidyl ether, and pentaerythritol tetraglycidyl ether. The process (I) also includes the following steps: The setting is such that the total mass [g] of (a), (b), and (c) is set as α, the number of moles of (d) is set as β, the total number of moles of water contained in (a), (b), and (c) is set as γ, and the total number of moles of methanol is set as δ, so that (β+γ+δ) / α is less than 10 μmol / g. The chlorine content is calculated using quantitative methods based on the intensity of fluorescence X-rays and the fundamental parameter method.
2. The method for manufacturing the polyacetal resin composition according to claim 1, wherein, The cyclic acetal compounds (b) and (b') are 1,3-dioxolane or 1,4-butanediol formaldehyde.
3. The method for manufacturing the polyacetal resin composition according to claim 1, wherein, The linear formaldehyde compound (d) is selected from at least one of the groups consisting of dimethoxymethane, diethoxymethane and dibutoxymethane.
4. The method for manufacturing the polyacetal resin composition according to claim 1, wherein, The melt flow rate of the linear polyacetal resin (B) is 1~50 g / 10 min.
5. A polyacetal resin composition manufactured by the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
Polyacetal resin composition
JP2003342442A
